Gandhi and Gulen : Comparing their views for peace building exercises - Alam, Anwar (Voices of Teachers and Teacher Educators, 2015)
Revered as ‘special person with divine grace’among their people at popular level, both Gandhiand Gulen envision a free, peaceful, democratic,tolerant and non-violent world and havegenerated positive public actions to achieve thisgoal through legal, peaceful and non-violentmeans. Though the world view of both are deeplygrounded in religious philosophy, Gandhi’s world view is primarily constructed through Santan Hindu religious tradition, while Gulen’s world view is primarily filtered through the prism of Sunni orthodox Islamic traditions with a focus on Turkish Islamic history. Gandhi, unlike Gulen,was not a product of religious seminary or hadundergone any scholastic training. On the otherhand, Gulen, unlike Gandhi, is neither a productof modern educational system nor a national-political leader of the masses -fighting for thepolitical liberation of people. Notwithstandingthe differences in the political context, time-periodand religious traditions and other semanticdifferences between the two, both are credited tohave conducted public actions on the basis of theirunderstanding of ‘religious truth’ in pursuit of afree, peaceful, democratic, tolerant and non-violent world through legal, peaceful and non-violent means